Perpaduan Algoritma Kriptografi Atbash dan Autokey Cipher dalam Mengamankan Data - Muhammad Fadlan; Rosmini Rosmini; Haryansyah Haryansyah (STMIK Budi Darma, 2021)
Data security is an important thing that must be done in the cyber era. The use of various kinds of digital technology in helping various human activities needs to be balanced with adequate data security. One of the ways that can be used in securing data is through cryptography. Atbash cipher is one of the cryptographic techniques used in securing data. However, this algorithm has a weakness because it only uses the process of reversing the position of the characters to be secured. This study proposes a cryptographic model that can maximize data security from the atbash cipher. The proposed model is a combination of the atbash cipher with the autokey cipher. The tests carried out on the proposed model have a 100% success rate, meaning that the encrypted message resulting from the proposed encryption process has been successfully restored to its original form through the proposed decryption process. The results of this study indicate that the atbash cipher cryptographic algorithm, combined with the autokey cipher algorithm can produce an encrypted message that is more difficult to crack.